ANALISIS DAN PERSEPSI PENGGUNA PARKIR STASIUN COMMUTER LINE DARU DI KABUPATEN TANGERANG - Habib, Nur Muhammad (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Daru station parking is a parking facility at Daru Station that is used by users of the Tanah Abang – Rangkas Bitung commuter line.The research aims to find out what things must be evaluated, and maintained against parking lots. The method used in this study consisted of direct observation methods and data processing using the IPA method. Based on the analysis that has been carried out, the parking space in this study is sufficient to accommodate four wheeled vehicles while based on user perceptions using the IPA method the parking space is considered good, but there are still aspects that need to be improved, namely the adequacy of parking space for two wheels, tha availability of roof coverings for vehicles and pavement in the parking are